Analisis Harga Terhadap Kepuasan Konsumen Di Angkringan Tempat Biasa Caffe - Mega Agustini; Annisa Dewita Putri; Lega Risma Alfioni; Nur Hikimah; Tina, Tina (FKIP, Universitas Palangka Raya, 2025)
Competition in the culinary business sector is increasingly intense, especially among modern cafés and angkringan, compelling business actors to continuously improve product quality, service, and marketing strategies to attract and retain customers. One of the key factors influencing customer satisfaction is price, which not only serves as an indicator of transaction value but also closely relates to customers’ perception of quality and purchasing power. This study aims to analyze the effect of price on customer satisfaction at Angkringan Tempat Biasa Café, a culinary business that offers a simple yet comfortable dining experience. The research employed a qualitative descriptive approach, utilizing in-depth interviews with consumers and supporting documentation collected over one month at the research location. The results indicate that prices perceived as reasonable and commensurate with the quality of food, service, and ambiance significantly enhance customer satisfaction. Conversely, price discrepancies relative to perceived benefits have the potential to reduce satisfaction and divert customers to alternative options. These findings underscore the importance of appropriate pricing strategies as a crucial business approach to foster customer loyalty and sustain business viability amid fierce competition. This research also contributes to the advancement of marketing management and consumer behavior knowledge, particularly in the culinary business context. Therefore, the management of Angkringan Tempat Biasa Café can utilize the findings as a basis for evaluating and formulating pricing policies and improving service quality to meet customer expectations and maintain a competitive position in the market